Clinical Implications for the Timely Diagnosis of Mycobacterium marinum in the Age of Biologic Therapy: A Case Report and Review of the Literature - Chris J. Lata; Kelle Edgar; Stephen Vaughan (Case Reports in Infectious Diseases)
Mycobacterium marinum infections typically present as cutaneous nodular lesions with a sporotrichoid lymphatic spread on extensor surfaces of extremities. The natural history of this infection can be altered if the host is immunosuppressed, leading to disseminated presentations. A detailed exposure history and high degree of suspicion for this indolent pathogen are often required for the correct diagnosis of this disease. We present a case of a 67-year-old male misdiagnosed with seronegative rheumatoid arthritis presenting with rheumatic nodules. Initiation of chronic immunosuppressant therapy including biologic monoclonal antibodies resulted in the exacerbation of initially localized disease to broadly disseminated lymphatic, joint, and myotendinous granulomatous disease and led to delay in the correct diagnosis. Cessation of immunosuppressants, with a prolonged course of antimicrobial therapy and multiple surgical debridements were required for cure.